Unionism and feminism: alliance building in the Brazilian Marcha das Margaridas - Teixeira, Marco Antonio; Campos Motta, Renata (Social movement studies, 2022)
Building on social movement analytics of coalition formation, we have established a dialogue with social theory on social inequalities and feminist scholarship on solidarity, bringing together the analytical sharpness of social movement studies with political and normative debates on solidarity building. We suggest that the processes of building solidarities that are key to coalition formation are best understood when taking into account four explanatory dimensions: context (structural conditions that might include political, economic, social and cultural institutional and various scales: from global events to national politics and organizational politics); discursive processes of framing that bridge across different social inequalities; the building of a coalitional identity and resources. We use this analytical framework to inquire into an instance of feminist coalitional politics, namely the Brazilian Marcha das Margaridas. This coalition emerged in the year 2000 and has had six editions since then, mobilizing between 20,000 to 100,000 women to Brasília. While the rural union movement forms the core of its leadership, several other partners co-organize the Marcha, including women's movements, trade union and agrarian social movements. The prominence of a union movement denotes the centrality of working class demands and redistributive issues together with demands for the recognition of gender difference and gender equality. We query the process of emergence and alliance building in the Marcha das Margaridas in 2000 by drawing on different types of data: documental analysis of archival material produced by the coalition, ethnographic fieldwork and semi-structured interviews with activists that represent different social movements in the coalition